Chitooligosaccharide Biguanide Repairs Islet β‐Cell Dysfunction by Activating the IRS‐2/PI3K/Akt Signaling Pathway in Type 2 Diabetic Rats. Issue 5 (14th February 2019) - Zou, Yalu; Wang, Yuanyuan; Zhang, Shengsheng; Wu, Yuntang; Liu, Xiaofei
Abstract: Islet β cell failure is a critical metabolic disorder in the development of type 2 diabetes (T2DM), and the decreased viability and dysfunction of β cells accelerate diabetic pathogenesis in association with higher mortality. In this study, the therapeutic effects of chitooligosaccharide biguanide (COSG), which is similar in structure to metformin and has negligible side effects, on islet β‐cell dysfunction and the possible mechanism are explored. Streptozocin‐induced diabetic rats are administered COSG via daily intragastric gavage for 8 weeks. COSG significantly controlled body weight loss, attenuated glucose levels in blood and urine, and increased serum insulin. Histological examination of the pancreas reveals that COSG also alleviated pancreatic atrophy in T2DM rats. Furthermore, COSG stimulated insulin receptor substrate‐2 (IRS‐2) signaling in rat islet β cells, thereby mediating the activation of the phosphatidylinositol 3 kinase/protein kinase (PI3K/Akt) signaling pathway. In addition, COSG promoted downstream forkhead transcription factor O1 (FoxO1) nuclear output to potentially activate pancreas duodenum homeobox‐1 (PDX‐1)/glucose transporter type‐2 (GLUT‐2)/glucose kinase (GCK) pathway‐regulated insulin secretion. COSG also inhibited the glycogen synthase kinase‐3β (GSK‐3β)/caspase‐3 pathway to prevent cell apoptosis. The intrinsic protective effects of COSG on the impaired insulin signaling system to delay β‐cell apoptosis, increase β‐cell growth and proliferation, improve β‐cell function and promote insulin secretion highlight the possibilities of COSG as a novel strategy for the prevention of T2DM. Abstract : COSG significantly controls body weight loss, attenuates glucose levels in blood and urine, increases serum insulin, and alleviates pancreatic atrophy in T2DM rats. Furthermore, COSG stimulates IRS‐2 signaling in rat islet β‐cells by mediating the activation of the PI3K‐AKT signaling pathway, which may activate the FoxO1/PDX‐1/GLUT‐2/GCK pathway to regulate insulin secretion, and inhibiting the GSK‐3β/caspase‐3 pathway to prevent cell apoptosis.